# Maths - Infinite series - Forum

 By: Magnus - magnus-skog Error in "Reorthogonalising a matrix"   2004-11-15 13:56 On the page "https://www.euclideanspace.com/maths/algebra/matrix/orthogonal/index.htm";    x^(-1/2) is approximated with the taylor series of the first order: (1 - x)/2, which is not correct.    The value x = 1 should give the same result but it's 1 and 0 (and a value of x = 1.01 even gives a negative approximation). The correct first order approximation should be 1 - (x - 1)/2 = (3 - x)/2    Regards  Magnus Skog
 By: Martin Baker - martinbaker RE: Error in "Reorthogonalising a matrix"   2004-11-16 09:10 Magnus,    Thanks very much, this is very useful.  I am not very familiar with taylors series, Since your message I have tried to derive the expression here:  https://www.euclideanspace.com/maths/algebra/polynomial/series/  this seems to work for f(1 + h) where h = 1 - x  Is this the correct way to do it?    Martin
 By: Magnus - magnus-skog RE: Error in "Reorthogonalising a matrix"   2004-11-16 10:25 Seems we need a Taylor crash course :)    The general Taylor formula (around the point x = a) can be written as follows:    f(x) = f(a) + (x - a) f'(a) + (x - a)^/2! f''(a) + (x - a)^3/3! f'''(a) (i)    And the special case when x = 0 is called Maclaurins formula:    f(x) = f(0) + x f'(0) + x^2/2! f''(0)+ x^3/3! f'''(0)    So there is no difference between the two of them, we have been doing Taylor  all along, but Maclaurin is just a special case of the more general Taylors  formula.    So in our example with f(x) = x^(-1/2) We get (just as you have gotten):    f(1) = 1  f'(1) = -1/2  f''(1) = 3/4    Substituting the values of the derivatives in (i) above yields:    f(x) = 1 - (x - 1)/2 + 3(x - 1)^2/8 - ...    So if we want to approximate x^(-1/2) with the first order taylor series,  we get:    x^(-1/2) ~~ 1 - (x - 1)/2 = (3 - x)/2
 By: Magnus - magnus-skog RE: Error in "Reorthogonalising a matrix"   2004-11-16 17:54 Read through your derived expression again.    "f(x + h) = f(x) + h f'(x) + h2/2! f''(x)+ h3/3! f'''(x) ...    f(1 + h) = f(1) + h f'(1) + h2/2! f''(1)+ h3/3! f'''(1) ...    f(1 + h) = 1 - h /2 + h2 3/8 ...    where h = 1 - x ???"    Take a look at the last row with f(1 + h), it is the same expression as mine, but you would want to evaluate it around h = 0. It gives the same result as evaluating mine around x = 1.    Regards  Magnus
 By: Martin Baker - martinbaker RE: Error in "Reorthogonalising a matrix"   2004-11-17 08:36 Magnus,    Many thanks again, I have updated both pages as you suggested.   I have also put examples here to check that it works:  https://www.euclideanspace.com/maths/algebra/matrix/orthogonal/reorthogonalising/    I still have some concerns about the derivation of [C] such as deciding that it is symmetric, but at least the expression appears to be correct.    I have also linked the pages to this thread if that is OK with you.    Martin
 By: Magnus - magnus-skog RE: Error in "Reorthogonalising a matrix"   2004-11-17 10:20 Of course it's ok :)    Just one minor correction left:    "f(1 + h) = 1 - h /2 + h2 3/8 ...    substituting h = 1 - x gives:"    It should be h = x - 1 =>    f(1 + h ) = f(1 + (x - 1)) = f(x) = 1 - (x - 1)/2 + ..    Otherwise it would be f(2 - x) = ..    Love your site and I will continue helping you if I can ! :)    Magnus

 metadata block see also: Correspondence about this page Book Shop - Further reading. Where I can, I have put links to Amazon for books that are relevant to the subject, click on the appropriate country flag to get more details of the book or to buy it from them. Engineering Mathematics - This book has been going for a long time and it is now in its 5th edition, so it is tried and tested. Other Math Books Specific to this page here:

This site may have errors. Don't use for critical systems.

Copyright (c) 1998-2017 Martin John Baker - All rights reserved - privacy policy.